Implementation of the User Centered Design Method in Designing UI/UX Prototypes for Traditional Herbal Medicine Sales - Annisa Rusydina Sabila; Asmunin (Journal of Applied Informatics Research, 2026)
This study aims to design a UI/UX prototype for a traditional herbal medicine sales application using the User-Centered Design (UCD) approach to improve user experience and usability. The study involved 96 respondents who were users or potential users of traditional herbal medicine products. The design process followed four stages of UCD: understanding the context of use, identifying user requirements, designing solutions, and evaluating the prototype. Usability evaluation was conducted using Cognitive Walkthrough (CW) to assess learnability and task efficiency, and the System Usability Scale (SUS) to measure user satisfaction. The results show that the prototype achieved a task completion rate of 92% in the Cognitive Walkthrough evaluation, indicating high learnability and efficiency. In addition, the prototype obtained an average SUS score of 82.3, which falls into the “Excellent” category and indicates a high level of user acceptance. These findings demonstrate that the implementation of the UCD method successfully produced a user-friendly interface that is effective, easy to understand, and aligned with user needs. This research contributes to the development of user-centered digital solutions for traditional herbal medicine commerce and supports the digital transformation of traditional product marketing.